2000
DOI: 10.1148/radiology.216.2.r00au12492
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Colorectal Obstruction Treated by Means of Self-expanding Metallic Stents: Effectiveness before Surgery and in Palliation

Abstract: Management of colorectal obstruction by using metallic stents was effective and safe, although colonic perforation is a potential complication. In cases of palliation, the method may obviate palliative colostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
115
1
15

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(139 citation statements)
references
References 19 publications
(26 reference statements)
8
115
1
15
Order By: Relevance
“…[15][16][17] We used 0.035-inch Teflon biliary guidewire (Zebra), and our technical success rate was comparable with recent published reports. [15][16][17] We compared the technical success, clinical efficacy, and complication rate according to stent types, covered and uncovered. Technical and clinical success rates were not significantly different in the 2 groups.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…[15][16][17] We used 0.035-inch Teflon biliary guidewire (Zebra), and our technical success rate was comparable with recent published reports. [15][16][17] We compared the technical success, clinical efficacy, and complication rate according to stent types, covered and uncovered. Technical and clinical success rates were not significantly different in the 2 groups.…”
Section: Discussionsupporting
confidence: 59%
“…[14][15][16][17] Initial studies reported a success rate of about 80%. The common cause of insertion failure was the inability of the guidewire to traverse the stricture and stiffness of stent delivery systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22][23][24] Whereas the most common etiology of technical failure was generally the inability to pass the guidewire through the obstruction site in colorectal cancer, 16 the most common cause of technical failure in our series was colonic immobilization. The etiologies of immobilization were thought to be adhesions around tissue caused by the previous surgeries and peritoneal seedings, which might make negotiation of endoscope more difficult around sharply angulated, tortuous, and fixed intestinal segments.…”
Section: Discussionmentioning
confidence: 71%